ADVANTAGES OF DIGITALIZATION OF LYCEUMS (Conferencea, 2022)
This article talks about the advantages of digitalization of lyceums. The article analyzes the current trends in the digital transformation of education for the purpose of training personnel for the digital economy. The impact of digitization on high school education is considered, and its positive and negative aspects for the modern educational environment are analyzed. The advantages of personalization and personalization of the learning process are presented.